Rearranging Equations

1 / 5

# Rearranging Equations - PowerPoint PPT Presentation

Rearranging Equations. Rearranging equations is based upon inverse functions. The four mathematical operations are in pairs:. + , -. Add and subtract operations are opposite to each other (inverse functions). × , ÷.

I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.

## PowerPoint Slideshow about 'Rearranging Equations' - baby

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

Rearranging Equations

Rearranging equations is based upon inverse functions

The four mathematical operations are in pairs:

+ , -

Add and subtract operations are opposite to each other

(inverse functions)

× , ÷

multiply and divide operations are opposite to each other

(inverse functions)

Rearranging Equations

The basic principal for rearranging equations is to look

at the operation that applies to a number or variable

apply the inverse function to move it to the other side

of the equation

Example:

to move the 3 to the other

side of the ‘=‘ apply the inverse

function.

x + 3 = y

The function is ‘+’, so the inverse function is ‘-’

-

x = y

+

3

Rearranging Equations

Example:

to move the 3 to the other

side of the ‘=‘ apply the inverse

function.

3x = y

The function is ‘×’, so the inverse function is ‘÷’

x = y

×

3

_

Rearrange this equation to make a the subject of the formula

3a = b

to have a on its own c and 3 need to be

on the other side of the ‘=‘

apply the inverse functions.

c

a = b

3

× c

Writing the equation like this with

a = something is called making a the

subject of the formula

c

÷ 3

Rearranging Equations

To summarise:

Multiply on one side of the equation goes to divide on the other side

a

x

y

=

b

Divide on one side of the equation goes to multiply on the other side

a

x

y

=

b

Add on one side of the equation goes to subtract on the other side

-

x = y

+

3

Subtract on one side of the equation goes to add on the other side

+

x = y

-

3

Rearranging Equations

Now try these:

Rearrange these to make y the subject of the formula

y = b - a

• 1. a + y = b
• 2. y – c = d
• xy = z
• e + 2y = f
• 2l + 5y = m
• 3y = h + i

y = d + c

y = z

x

y = f - e

y = m – 2l

y = h + i

2

3

5